Is low-dose intratympanic gentamicin an effective treatment for Ménière's disease: the Birmingham experience. Issue 10 (October 2015) - Watson, G J; Nelson, C; Irving, R M
Abstract Background: Since the development of intratympanic aminoglycoside in the 1950s, otologists have been able to chemically ablate the vestibule. We present the results of using low-dose intratympanic gentamicin to treat Ménière's disease. Method: A retrospective review was performed of all patients who underwent low-dose intratympanic gentamicin therapy over seven years. Data on gender, age, number of procedures, pure tone audiometry and symptom control were analysed. Results: In all, 38 patients underwent low-dose intratympanic gentamicin therapy. These comprised 25 females and 13 males, with an average age of 58.4 years. Hearing was preserved in 87.5 per cent of patients, with no significant difference before and after treatment (p = 0.744). In all, 85.7 per cent of patients had complete or substantial symptom control (classes A and B, respectively). Conclusion: Low-dose intratympanic gentamicin therapy was effective in controlling the symptoms of Ménière's disease patients, while preserving hearing.